Satisfaction as A Determination Of Muhammadiyah Members Loyalty In South Sumatera - Rahayu, Sri; Asiati, Diah Isnaini (Universitas muhammadiyah palembang, 2020)
Loyalty has a very important meaning for the sustainability of the Muhammadiyah Association. Muhammadiyah member's loyalty will automatically strengthen and enlarge the existence of the organization through the various propaganda activities it developed. The purpose of the study was to see the effect of satisfaction on Muhammadiyah's loyalty members. The study was developed using an associative design involving two variables, namely member's loyalty, and member's satisfaction. Each variable was developed into 18 and 16 indicators, respectively. The population was determined by all Muhammadiyah members in South Sumatra who had Muhammadiyah Standard Number (NBM- Nomor Baku Muhammadiyah) of 6,617 people. The number of samples was determined as much as 5% of the population of 232 members by cluster sampling. The determination of clusters was based on districts spread across South Sumatra. The main data used primary data with questionnaire data collection methods. The analysis technique used simple regression. The results of the study showed that member's satisfaction significantly influences Muhammadiyah's loyalty members in South Sumatra.